Some Aspects of Pinus Caribaea Mor. Var. Hondurensis Barr. and Golf. Nutrition in Peninsular Malaysia - Zainorin, Abang Naruddin (1981)
Three approaches were employed to study some nutritional aspects of Pinus caribaea var. hondurensis namely, soil analysis, soil bio-assay and foliar analysis. Five soil composites each from Kemasul (Pahang) and ulu Sedili (Johore) plantation areas were analysed for physic al and chemical properties. For pot culture, a 2²x 6 factorial experiment using soil collected from Kemasul was conducted to study the effects of nitrogen, phosphorus and potassium on the growth of p. caribaea var. hondurensis seedlings. Nitrogen and potassium were applied at levels equivalent to 0 and 112 kg/ha; and phosphorus at 0, 168 kg/ha, 336.2 kg/ha, 504 kg/ha, 672.2 kg/ha and 840.3 kg/ha. At the end of the experiment, dry weight of roots, stems and needle s were determined. Needles were analysed for N, P and K contents. Simultaneously, two randomised complete block fertiliser trials were laid out in the field. Nitrogen and potassium were applied at 0 and 224 kg/ha each while phosphorus was given at 0, 336.2 kg/ha, 672.2 kg/ha and 1008.3 kg/ha levels. Needles from these plants were collected at three times to concide with dry (February - May), transitional (June - september) and wet (October - January) seasons from five positions in the crown. The study shows that phosphorus is highly deficient at both the sites. Application of p.fertiliser at the rate of about 340 kg/ha at Ulu Sedili and about 504 kg/ha at Kemasul would be desirable for optimum gorwth of P. caribaea var. hondurensis seedlings.